Superoutro de Edgard Navarro e o processo de transição da abertura política no Brasil - Freire, Taís Rodrigues (Universidade Federal de São Carlos, 2018)
This research examines the film Superoutro (1989), by Edgard Navarro, which recovers the films developed by the director in the 1970s and points out issues that reflect the period of political and cultural transition, soon after the political opening in Brazil. The main objective of research is to analyze the film in order to understand how the transformations occurred in the democratization process in Brazil, after the military dictatorship established in 1964. The study was conducted in two methodological steps: film analysis, which includes the analysis of film's internal structure and external analysis, both supported by literature review, incluinding topics based on the film and in method of film analysis.
Superoutro of Edgard Navarro and the process of transition of political opening in Brazil
Keywords: Edgard Navarro; Superoutro; Cinema experimental; Cinema baiano; Super-8; Experimental cinema; Bahian cinema; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA